Effects of couple-based violence prevention education on male partners' knowledge, attitudes and controlling behavior related to intimate partner violence in rural Ethiopia: a cluster randomized controlled trial - Agde, Zeleke Dutamo; Magnus, Jeanette H.; Assefa, Nega; Wordofa, Muluemebet Abera (Frontiers in Public Health, 2025)
BackgroundSupportive attitudes toward wife-beating and the experience of controlling behavior from husbands have been known to increase the risks of intimate partner violence (IPV). The aim of this study was to determine the effects of couple-based violence prevention education in addressing IPV-related knowledge, attitudes, and controlling behavior among male partners in rural Ethiopia.MethodA cluster randomized controlled trial was conducted using a two-arm parallel group design. The 16 clusters were randomly allocated into 8 intervention groups and 8 control groups. A total of 432 couples (432 male partners and 432 pregnant wives) participated in the trial. Couple-based violence prevention education (CBVPE) was provided to the participants in the intervention group, while the control group received routine or standard care. Difference-in-difference analysis and the Generalized Estimating Equation (GEE) model were used to assess the effectiveness of the intervention.ResultAt the endline, 94.4% of male partners in the intervention group and 94.9% in the control group were available for the intention-to-treat analysis. Male partners in the intervention group were 3.7 times more likely to have good knowledge about IPV compared to male partners in the control group (AOR = 3.7; 95% CI 2.6–5.4). Male partners in the intervention group were 67.6% less likely to report supportive attitudes toward wife–beating compared to those in the control group (AOR = 0.324; 95% CI 0.229–0.459). Also, the proportion of controlling behavior exhibited by male partners in the intervention group was 56.4% less compared to the control group (AOR = 0.436; 95% CI 0.317–0.600).ConclusionThe intervention proved effective in enhancing knowledge about IPV, reducing supportive attitudes toward wife-beating, and curbing controlling behaviors among male partners in the study setting. This approach holds promise for scaling up and adapting to similar contexts in Ethiopia.Trial registrationThe trial was registered on ClinicalTrials.gov with the identifier NCT05856214 on May 4, 2023.